2011
DOI: 10.5433/1679-0359.2011v32n1p295
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies against bovine respiratory syncytial virus (BRSV) in dairy cattle with different prevalences of bovine herpesvirus type 1 (BoHV-1) in São Paulo State, Brazil

Abstract: Serum samples from three dairy farms classified as high (1, 78.6%), medium (2, 40.0%) and low (3, 1.6%) prevalence for bovine herpesvirus type 1 (BoHV-1) from São Paulo State, were collected to analyze the prevalence to the bovine respiratory syncytial virus (BRSV) by virus neutralization test. The BRSV observed prevalences for farms 1, 2, and 3 were 45.61%, 84.42%, and 54.09%, respectively. Farm 2 showed higher prevalence to BRSV (P < 0.0001) than farms 1 and 3, which were equivalent (P = 0.2291). Two risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
1
4
0
7
Order By: Relevance
“…Los agentes virales son considerados agentes primarios y factores determinantes para las infecciones bacterianas secundarias, ya que alteran el funcionamiento de las células del sistema inmunitario, de la mucosa respiratoria y la producción de citocinas (Bosch et al, 2013), entre los patógenos relacionados con las SRB. Los virus de la diarrea vírica bovina (VDVB), el herpesvirus bovino tipo 1 (HVBo-1), el virus respiratorio sincitial bovino (VRSB)y el vírus de parainfluenza tipo 3 (PI-3) se incluyen entre la etiología de este problema, siendo considerados como los principales agentes víricos (Brito et al, 2010;Affonso et al, 2011;Gaeta et al,2017). El VDVB pertenece a la familia Flaviviridae y está relacionado con otras patologías como diarrea, enfermedad de las mucosas y abortos (Lanyon et al, 2014;OIE, 2015).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Los agentes virales son considerados agentes primarios y factores determinantes para las infecciones bacterianas secundarias, ya que alteran el funcionamiento de las células del sistema inmunitario, de la mucosa respiratoria y la producción de citocinas (Bosch et al, 2013), entre los patógenos relacionados con las SRB. Los virus de la diarrea vírica bovina (VDVB), el herpesvirus bovino tipo 1 (HVBo-1), el virus respiratorio sincitial bovino (VRSB)y el vírus de parainfluenza tipo 3 (PI-3) se incluyen entre la etiología de este problema, siendo considerados como los principales agentes víricos (Brito et al, 2010;Affonso et al, 2011;Gaeta et al,2017). El VDVB pertenece a la familia Flaviviridae y está relacionado con otras patologías como diarrea, enfermedad de las mucosas y abortos (Lanyon et al, 2014;OIE, 2015).…”
Section: Resultsunclassified
“…Las muestras fueron centrifugadas a 600 x g durante 15 minutos y el suero obtenido fue guardado en viales conservados a -20 ° C hasta su procesado. La identificación de anticuerpos se realizó por medio de la técnica de neutralización de acuerdo con OIE (2010) y OIE (2015) para HVBo-1 y VDVB respectivamente y de acuerdo con Affonso et al (2011) para VRSB. Cepas de VDVB-Ia NADL, cepa BoHV-1 Los Ángeles y ATCC VR-1485 se utilizaron como controles positivos.…”
Section: Materiales Y Métodosunclassified
“…In our research, the occurrence of antibodies against BRSV (Ab-BRSV) was 37.4%. Affonso et al, (2011) reported prevalence ranged from 45.61% to 84.42% in São Paulo State. In different locations in the same state, Oliveira et al (2016) detected 93.10%.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies reported BRSV infection in cattle (Driemeier et al 1997), only one describes the occurrence of antibodies against BRSV in Brazil. In São Paulo State, Affonso et al (2011) observed prevalence between 46% and 84%, which suggests its importance to the respiratory diseases in this state.…”
Section: Introductionmentioning
confidence: 90%
“…Even though, the occurrence of other subgroups in Brazil may not be disregarded, as the number of BRSV isolates characterized until now is very small. In Brazilian herds, BRSV was first detected from lung tissues of slaughtered calves from Southern region (GONÇALVES et al, 1993) and then some serological surveys showed that BRSV infections are spread in animals from Southern and Southeastern regions, reaching high prevalences (CAMPALANS; AFFONSO et al, 2011). Nevertheless, the high serological prevalence compared to low incidence of clinical disease may indicate that most of infections in Brazilian herds are subclinical, hindering control measures for the disease.…”
Section: Introductionmentioning
confidence: 99%